2004
DOI: 10.1248/bpb.27.753
|View full text |Cite
|
Sign up to set email alerts
|

Conditionally Immortalized Syncytiotrophoblast Cell Lines as New Tools for Study of the Blood-Placenta Barrier

Abstract: Syncytiotrophoblasts play an essential role in restriction of drug delivery through the blood-placenta barrier (BPB). Conditionally immortalized syncytiotrophoblast cell lines, TR-TBTs, were established at gestational day 18 from pregnant transgenic rats (Tg-rats) harboring the temperature-sensitive SV 40 (ts SV40) large T-antigen. TR-TBTs exhibit temperature-sensitive cell growth due to the expression of SV 40 large T-antigen, and thus the cell growth can be regulated by changing the culture temperature. TR-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 78 publications
0
35
0
2
Order By: Relevance
“…We previously reported that the mRNA expression of various transporters and the localization of GLUT1 and GLUT3 in TR-TBTs are comparable to those in rat placenta. 14,15) These data suggested that TR-TBTs may be good model of rat syncytiotrophoblasts for analysis of the localization and the protein expression of transporters and anchoring proteins in blood-placenta barrier.…”
Section: Immunohistochemical Analysis Of Ezrin In Rat Placentamentioning
confidence: 93%
See 3 more Smart Citations
“…We previously reported that the mRNA expression of various transporters and the localization of GLUT1 and GLUT3 in TR-TBTs are comparable to those in rat placenta. 14,15) These data suggested that TR-TBTs may be good model of rat syncytiotrophoblasts for analysis of the localization and the protein expression of transporters and anchoring proteins in blood-placenta barrier.…”
Section: Immunohistochemical Analysis Of Ezrin In Rat Placentamentioning
confidence: 93%
“…Total cellular RNA was prepared from PBS(Ϫ)-washed cells or tissues using an RNeasy Mini Kit (QIAGEN Sciences) according to the manufacturer's instructions. cDNA was synthesized from 1 mg of total RNA using oligo (dT) 15 as a primer, with molony murine leukemia virus (M-MLV) reverse transcriptase (RT) (ReverTraAce, Toyobo Co., Ltd., Osaka, Japan) for TR-TBT cells and Superscript III (Invitrogen) for rat placenta. Real-time PCR analysis was performed using an ABI PRISM 7700 sequence detector system (PE Applied Biosystems, Foster City, CA, U.S.A.) with 2X SYBR Green PCR Master Mix (PE Applied Biosystems) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…vM = vellosidades en lado materno de la placenta; stB = sinsiciotrofoblasto; ctB = cito-trofoblasto; ecF = endotelio del capilar del lado fetal de la placenta. (detalles en el texto) 26,27,46 . Figura 3. la hipótesis de Pedersen en forma gráfica 19 .…”
Section: Fisiopatología Tradicional De La Macrosomía En Dmg: La Hipótunclassified